Influence of Loop Length on Microcapsule Distribution in Cotton Interlock Knitted Fabric - Dao, Thi Chinh Thuy; Chu, Dieu Huong (Old Journal, 2020)
Functional textile using microcapsules has been taken lots of interest all over the world. Along with microcapsules, the textile substrate contributes important part to the performance of end use products. This study was to investigate the effect of loop length on the microcapsule distribution in cotton interlock knitted fabric. Four levels of loop length studied were 2.83, 2.87, 2.96 and 3.05 mm. Microcapsules were applied to fabrics by coating technique. The microcapsule distribution in the treated fabric was expressed by the average area of microcapsule aggregates on the fabric surface, which was determined by Meander 3.1.2 software of Peacock Media on the SEM images. The results showed an increase of microcapsule aggregate area in the order of 7537, 8600, 13379 and 16020 µm² for the loop length of 2.83, 2.87, 2.96 and 3.05 mm, respectively. This revealed the less even distribution of microcapsules at the higher loop length. The principle of coating technique, as well as the higher porosity of the fabric at higher loop length, were thought to account for this trend.